Nitroheterocyclic derivatives: privileged scaffold for drug development against Chagas disease - Benito Scarim, Cauê [UNESP]; Man Chin, Chung [UNESP] (Springer Nature, 2019)
Chagas disease or American trypanosomiasis is a major public health problem in Latin America. Approximately seven million people are currently infected worldwide. Despite the efforts to develop new drugs, only two nitroheterocyclic drugs (nifurtimox and benznidazole) are available for the treatment of Chagas disease, These drugs have been available since the 1970s, and no new drugs have been approved. Due to the lack of alternatives for the treatment of this disease, this review describes recent advances (2013–2019) concerning nitroheterocyclic compounds with activity against T. cruzi parasites, as well as new perspectives for future research.
Keywords: Chagas disease; New drugs; Nitro compounds; T. cruzi